2022
DOI: 10.1039/d2qo01329k
|View full text |Cite
|
Sign up to set email alerts
|

Iron–iodine co-catalysis towards tandem C–N/C–C bond formation: one-pot regioselective synthesis of 2-amino-3-alkylindoles

Abstract: Herein, we report a novel iron and iodine cooperative catalytic system for intermolecular C2,3−H aminoalkylation of indoles with azoles and xanthenes as the coupling agents, which allows tandem C−N/C−C bond...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…303 Thereafter, Liang and co-workers reported the Fe/iodine cocatalyzed C(sp 3 )−H heteroarylation of xanthenes with indoles and azoles as coupling partners in 2022 (Scheme 32e). 304 These reactions allowed tandem C−N/ C−C bond formation for the regioselective synthesis of 2amino-3-alkylindoles .…”
Section: Radical Substitution Of Fe Complexesmentioning
confidence: 99%
“…303 Thereafter, Liang and co-workers reported the Fe/iodine cocatalyzed C(sp 3 )−H heteroarylation of xanthenes with indoles and azoles as coupling partners in 2022 (Scheme 32e). 304 These reactions allowed tandem C−N/ C−C bond formation for the regioselective synthesis of 2amino-3-alkylindoles .…”
Section: Radical Substitution Of Fe Complexesmentioning
confidence: 99%
“…Accordingly, the C(sp 3 )–H functionalization at the 9-position of these molecules remains a continuous area of interest for synthetic chemists. Recently, the direct construction of C(sp 3 )–C, C(sp 3 )–N, and C(sp 3 )–S bonds for the synthesis of 9-substituted xanthene derivatives has been realized by Cozzi, 3 Klussmann, 4 Jiao, 5 Yorimitsu, 6 Pericàs, 7 Zeng, 8 Loh, 9 Chen, 10 Li, 11 Gong, 12 Li, 13 Deb, 14 Wang, 15 and Liang 16 by using different strategies including transition metal catalysis, oxidative dehydrogenative cross-coupling, photoredox catalysis, and electrolysis. On the other hand, organophosphorus compounds bearing C(sp 3 )–P bonds have been of particular interest due to their broad applications in organic synthesis, medicinal chemistry, agrochemicals, flame retardants, and extractants.…”
mentioning
confidence: 99%
“…The use of MsOH or TfOH instead of TsOH resulted in a lower yield (entries 14 and 15). Control experiments showed that visible light, PC, and the oxygen atmosphere are critical to the success of the reaction (entries [16][17][18]. Although the reaction could proceed under an air atmosphere, 3aa was obtained in a poor yield (entry 19).…”
mentioning
confidence: 99%